AMERIKA SERIKAT, ISLAM DAN INDONESIA - Barry, Robert L. (Jurnal Bestari, 1994)
There are there important theme faced by USA related to the Islamic world. First of all, concerning the issue whether the cold war era will be signified by the conflict of civilization between West and Islamic world. Second, about the dramatic short cut and new chalange arose in the effort to finish the solution peacefully and wisely throughout the Middle East. Third, the effort to finish the ethnic and communal conflict in bosnia.